ИЗМЕНЕНИЕ ПРОНИЦАЕМОСТИ ЭРИТРОЦИТАРНЫХ МЕМБРАН ПРИ ДЕЙСТВИИ ЧЕТЫРЕХХЛОРИСТОГО УГЛЕРОДА И РАСТИТЕЛЬНОГО ПРЕПАРАТА (Experimental biology, 2009)
There are results of investigations of changes of erythrocyte membrane permeability at influence of carbon tetrachloride and possibility of prevention damaging action of hepatotoxicant by phytopreparation.
Keywords: erythrocyte membrane; hepatotoxicant by phytopreparation